2015
DOI: 10.1016/j.micinf.2015.03.001
|View full text |Cite
|
Sign up to set email alerts
|

IRF3 deficiency impacts granzyme B expression and maintenance of memory T cell function in response to viral infection

Abstract: The role of interferon regulatory factor 3 (IRF3) in the innate immune response to infection has been well studied. However, less is known about IRF3 signaling in shaping the adaptive T cell response. To determine the role of IRF3 in the generation and maintenance of effective antiviral T cell responses, mice deficient in IRF3 were infected with a potentially persistent virus, Theiler’s murine encephalomyelitis virus (TMEV) or with a model acute infection, influenza A virus (IAV). IRF3 was required to prevent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 51 publications
1
17
0
Order By: Relevance
“…However, IRF3 deficiency impaired expression of splenic IFN-γ at this time. Previously, we found that T cells from IRF3KO mice had significant impairments in T cell IFN-γ during the response to Influenza A virus infection compared with wild-type mice [19]. These data strongly suggested that IRF3 plays a significant role in expression of IFN-γ from T cells.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…However, IRF3 deficiency impaired expression of splenic IFN-γ at this time. Previously, we found that T cells from IRF3KO mice had significant impairments in T cell IFN-γ during the response to Influenza A virus infection compared with wild-type mice [19]. These data strongly suggested that IRF3 plays a significant role in expression of IFN-γ from T cells.…”
Section: Discussionmentioning
confidence: 72%
“…Previously, we reported that IRF3 contributes to IFN-γ expression from effector T cells during antiviral immune responses [19]. To determine the dynamics of IFN-γ expression we injected B16F10 cells into C57Bl/6 mice and quantified IFN-γ in spleens and tumors by qRT-PCR and ELISA, respectively, during tumor growth.…”
Section: Resultsmentioning
confidence: 99%
“…We previously reported that IRF3 deficiency in mice impairs IFN-γ and GrB expression from memory T cells following infections with Influenza A virus or Theiler’s virus (11). To determine if these impairments include other T cell factors, such as IL-17, we stimulated T cells of splenic mononuclear populations from C57Bl/6 or IRF3KO mice with anti-CD3 with or without anti-CD28 in the presence or absence of poly I:C, a TLR3 agonist.…”
Section: Resultsmentioning
confidence: 99%
“…However, recent studies have uncovered an unexpected link between IRF3 and T cell immune responses in mice during infection (10, 11) and during responses to antigens (12). We recently reported that mice deficient in IRF3 had impairments in memory T cell expression of GrB and IFN-γ during T cell responses to Influenza A and Theiler’s virus infection (11). This role for IRF3 in T cells responses may be the result of IRF3 activation in APCs that participate in T cell responses, where it transcriptionally regulates expression of APC cytokines governing T cell differentiation during the response.…”
Section: Introductionmentioning
confidence: 99%
“…Type I interferons such as IFN-α signal through STAT2; STAT2-deficient mice exhibit significantly reduced GzmB expression in lung CD4 T cells following influenza infection, supporting the role of this pathway in generating CD4 CTL in vivo . Loss of interferon regulatory factor 3 also impairs GzmB expression and CD4 memory cells (82), providing further evidence for the involvement of interferon signaling in CTL induction. Workman et al have also suggested that inflammatory cytokines such as IL-6 in the lung microenvironment may promote CD4 CTL activity, similar to the way in which CD8 CTL require signals from DCs and IL-15 during influenza infection (79).…”
Section: Mechanisms Regulating Cd4 Ctl Developmentmentioning
confidence: 92%